2021
DOI: 10.1111/1753-0407.13233
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of gestational diabetes mellitus in the associations of maternal prepregnancy body mass index with neonatal birth weight

Abstract: Background: Both prepregnancy obesity and gestational diabetes mellitus (GDM) have been linked to adverse neonatal birth weight. However, the mediating role of GDM between prepregnancy obesity and neonatal birth weight is unclear. Method: The cohort study included 17 260 singleton pregnant women and their newborns. Participants' demographic characteristics, disease history, family history of the disease, and the perinatal outcomes were recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…It could be considered as excess GWG. Except for GWG, prior studies 34 36 considered that pre-pregnancy BMI was a stronger predictor of adverse pregnancy outcomes. Our previous study 16 found that Chinese GDM women with underweight at a higher risk of SGA.…”
Section: Discussionmentioning
confidence: 99%
“…It could be considered as excess GWG. Except for GWG, prior studies 34 36 considered that pre-pregnancy BMI was a stronger predictor of adverse pregnancy outcomes. Our previous study 16 found that Chinese GDM women with underweight at a higher risk of SGA.…”
Section: Discussionmentioning
confidence: 99%
“…Bu bilgi, obez gebelerin doğum planının yapılması ve yenidoğan bakımı konusunda karşılaşılabilecek sorunların öngörülmesi açısından önemlidir. Ayrıca bu bilgi, doğum ağırlığı daha yüksek olan çocukların yetişkinlik döneminde de obez olma eğiliminde oldukları için, 0-5 yaş çocuk izlemi açısından da önemlidir (71).…”
Section: Discussionunclassified
“…• Gestational diabetes: Defined as FBG 5.1 mmol/L, 1 hour plasma glucose 10.0 mmol/L, or 2 hours plasma glucose 8.5 mmol/, according to the international diabetes and pregnancy research group criteria [20].…”
Section: Inclusion Criteriamentioning
confidence: 99%